American society of clinical oncology update on the role of bisphosphonates and bone health issues in women with breast cancer Part II. Bisphosphonates in the adjuvant therapy of breast cancer - I. V. Vysotskaya (ABV-press, 2014)
American society of clinical oncology update on the roleof bisphosphonates and bone health issues in women with breast cancer Part II. Bisphosphonates in the adjuvant therapy of breast cancer